Physical Model of Vertical Water Movement Inside a Soil-Column Apparatus for Infiltration Study with A Two-Way Orientation Approach - Fajar, Reza Adhi; Handayani, Gunawan; Notosiswoyo, Sudarto; Widodo, Lilik Eko; Pamungkas, Tri Chandra (ITB Journal Publisher, LPPM ITB, 2019)
To improve the theory of Richard?s equation, studying infiltration under free-draining conditions at the ground surface is necessary. Verification is required to clarify the physical model of water movement. The aim of this study was to describe multistage measurements of both the wetting and the drying front scheme of one-dimensional infiltration at laboratory scale. A soil-column infiltration apparatus was built consisting of a double acrylic wall, a sensor set and a light bulb. Acrylic was chosen as the material for the wall to minimize possible heat conduction on the wall side, which was wrapped in double insulation to achieve adiabatic condition. The following three main sensors were used and controlled by a microcontroller: water-content, pressure and temperature sensors. Meanwhile, the light bulb at the top of the apparatus was set to non-isothermal condition. The instrument was successfully built to describe vertical water movement. Slight modifications were carried out to ensure more precise observation. This resulted in the initiating of new shape interpretation based on the water-ponding measurement to refine the simplified pattern that was introduced by the conventional Green-Ampt theory.